Time Warner - Fitzgerald, Scott (2016)
Time Warner remains one of the leading corporations in the global media industry. For the majority of the last decade of the 20th century and the first decade of the new millennium, this U.S.-based firm ranked as the world’s largest media corporation. This position build on a history of corporate acquisitions and expansion in a range of communication and cultural industries, which appeared to be secure at the beginning of the 21st century following the formation of AO-Time Warner. Yet over the last decade Time Warner has stepped back from the forms of conglomeration that were synonymous with its growth and divested many of its operations. While remaining highly successful and culturally significant, its current operations, adjusting for inflation, only produce approximately half of its 2001 revenues. Its 2014 revenues ($27.36 billion) ranked 8th behind Comcast, Google, The Walt Disney Company, News Corp/21st Century Fox, DirecTV, and National Amusements (Viacom/CBS).1 In 2014, Rupert Murdoch’s 21st Century Fox sought to acquire more critical mass in a rapidly consolidating media and communications environment by making an $80 billion bid for Time Warner and its cable networks, filmed entertainment operations, and sports rights.Time Warner quickly rejected the bid: Jeffrey L. Bewkes, the corporation’s current CEO and Chairman, reassured it’s stockholders that such a “game-changing transaction” was unnecessary: “Our scale, our brands, [and] the management…put us in a position to capitalize on the trends in the world…[especially] a very strong growing demand for high-quality video content.”2 How is Time Warner positioned today in terms of the size of its operations and the scope of its cultural commodities? What are the goals and strategies of its management? How has Time Warner’s de-conglomeration affected both the type of operations it runs and the power it has within international commodity chains? To answer these questions, it is necessary to review the company’s current organization and development. This chapter starts with a brief history of Time Warner and the two companies from which it emerged, Time Inc. and Warner Communications Inc. It then presents an overview of the company’s more recent economic, political, and cultural activities.